1997
DOI: 10.1074/jbc.272.39.24170
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Calcium-independent Mannose 6-Phosphate Receptor Incorporation into trans-Golgi Network-derived Clathrin-coated Vesicles by Wortmannin

Abstract: The transport of pro-cathepsin D from the trans-Golgi network (TGN) to the endosomal pathway is dependent on binding to the calcium-independent mannose 6-phosphate receptor (ci-M6PR), which is incorporated into TGN-derived clathrin-coated transport vesicles (CCVs). Inhibition of this transport step by wortmannin has led to the proposal that it is dependent upon a phosphoi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 37 publications
4
17
0
Order By: Relevance
“…Wortmannin inhibited the delivery of cathepsin D to lysosomes (28,72) apparently through an effect on the sorting of cargo into vesicles rather than through an inhibition of vesicle budding. Wortmannin had only a minor effect on the production of small vesicles from trans-Golgi network (TGN) membranes but prevented the mannose 6-phosphate receptor from entering into vesicles (110). However, yeast Vps34p or mammalian PtdIns3K have not been shown to be located on Golgi or TGN membranes.…”
Section: Ptdins3k and Vps34pmentioning
confidence: 99%
See 1 more Smart Citation
“…Wortmannin inhibited the delivery of cathepsin D to lysosomes (28,72) apparently through an effect on the sorting of cargo into vesicles rather than through an inhibition of vesicle budding. Wortmannin had only a minor effect on the production of small vesicles from trans-Golgi network (TGN) membranes but prevented the mannose 6-phosphate receptor from entering into vesicles (110). However, yeast Vps34p or mammalian PtdIns3K have not been shown to be located on Golgi or TGN membranes.…”
Section: Ptdins3k and Vps34pmentioning
confidence: 99%
“…PtdIns3K inhibitors were found to disrupt the sorting of lysosomal proteins in the Golgi, and this was interpreted to mean that the site of PtdIns3K action was the TGN (31,72). A PtdIns3K activity was found to be required for budding of vesicles containing the polyimmunoglobulin receptor from isolated rat hepatocyte Golgi membranes (169), and wortmannin was observed to inhibit the sorting of mannose 6-phosphate receptors (M6PRs) into vesicles, but not the budding of vesicles, from the TGN (110). Wortmannin treatment also altered the morphology of the TGN (139).…”
Section: Ptdins(3)p On the Golgimentioning
confidence: 99%
“…By contrast, we observed a strong inhibition of the starvation-induced redistribution of mAtg9 with a PtdIns 3-kinase inhibitor. It has been shown that PtdIns 3-kinase is required for the exit of CI-MPR (Gaffet et al, 1997). Furthermore, it has been reported that there may be an inhibitor-sensitive endosomal trafficking step, involving CI-MPR, which is not mediated by type III PtdIns 3-kinase (Row et al, 2001).…”
Section: Localization and Topology Of Matg9mentioning
confidence: 99%
“…Interestingly, vesicles from the TGN and plasma membrane may intersect at the endosomal-TGN network-the site of Nef/ MHC-I accumulation (14,22,33,44), and a known site of PACS-1 activity (29,48). PI 3-kinase, a regulator of TGN-toendosome/lysosome trafficking (3,8,11), is necessary for Nef's effects on MHC-I (44), providing additional evidence for the role of this pathway. The ability of Nef to affect the trafficking of MHC-I at both the TGN and the plasma membrane would maximize the effects of Nef on antigen presentation and escape of HIV-infected cells from CTL killing.…”
Section: Hiv-1 Nef Associates With Mhc-i In Vivomentioning
confidence: 99%